The Influence Of Larvae-Free Rate (ABJ) On The Incidence Of Dengue Fever Cases In The Work Area Of UPTD Puskesmas Juanda, Samarinda City - Ninik, Ninik Arifah; Rusdi, Rusdi; Ainur Rachman (Jurnal EduHealth, 2024)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection transmitted through the bite of the Aedes aegypti mosquito. This disease has clinical manifestations of bleeding, which can lead to shock and death. Controlling DHF has become a national priority due to the increasing spread of the disease and the frequent occurrence of outbreaks. Delayed treatment is often a major cause of the high mortality rate. Therefore, preventive efforts are crucial to reducing the incidence of DHF. This study aims to determine the influence of the Larvae-Free Index (LFI) on the incidence of DHF in the working area of the UPTD Puskesmas Juanda. The research population includes residents of RT in Air Hitam and Gunung Kelua subdistricts affected by DHF, with a total sample of 99 respondents. The study employed a survey method using questionnaires and a cross-sectional research design. Data analysis using Fisher's Exact test showed a significant correlation between LFI values and DHF cases (p-value = 0.04). These findings indicate that increasing LFI can contribute to reducing the incidence of DHF. This study highlights the importance of implementing mosquito breeding eradication programs (PSN) to improve LFI as a preventive measure in DHF control.